Skeletal and respiratory muscle oxygen transport in pulmonary hypertension - Schulze, Kiana Marie (My University, 2025)
Pulmonary hypertension (PH) is a disease characterized by pulmonary vascular remodeling and elevated pulmonary arterial pressures which subsequently impairs gas exchange in the lungs and eventually, right ventricular function. Hallmarks of PH include dyspnea and exercise intolerance which, despite previous notions, is not solely attributable to cardiopulmonary dysfunction. In these investigations, we sought to determine whether skeletal and respiratory muscle blood flow and vascular function are impaired in PH at rest and during contractions or exercise. Specifically, we used intravital microscopy, fluorescent microspheres, and pressure myography to explore these questions in a monocrotaline rat model of PH. Our findings demonstrate that resting and exercising blood flow and oxygen transport are lower in skeletal muscle via convective and diffusive impairments in PH compared with healthy controls. In respiratory muscle (i.e., the diaphragm), PH rats display a regional redistribution toward the ventral and crural regions of the diaphragm during contractions and submaximal exercise. These regions are not expected to contribute as greatly to ventilatory work and this observation therefore unveils a mechanism potentially underlying diaphragmatic weakness and failure in PH. Our findings suggest that the medial costal diaphragm arterioles are less reactive, both to vasodilatory stimuli as well as changes in intraluminal pressure, which may help explain the basis for this regional redistribution. Finally, we’ve found that there is a heightened diaphragm blood flow during submaximal exercise in PH compared with healthy animals that is concurrent with a lower skeletal muscle blood flow. This redistribution of blood flow toward the diaphragm and away from working muscle during exercise is likely related to diaphragm vascular dysfunction and exercise intolerance. As such, these derangements may provide a specific target for therapeutic interventions that could potentially normalize muscle blood flow distribution to that of healthy individuals and help ameliorate exercise intolerance. This body of work provides novel insights into skeletal and respiratory muscle oxygen delivery alterations at rest and during exercise in PH, providing evidence for oxygen transport-related mechanisms that may predicate both dyspnea and exercise intolerance in PH. Future directions will hopefully assess targeted therapeutic strategies aimed at improving diaphragm vascular function with the goal of restoring blood flow and oxygen delivery, improving O2 delivery-to-O2 demand matching and improving the quality of life and prognosis in PH.
Keywords: Monocrotaline; Cardiovascular; Exercise; Diaphragm; Microvasculature